Creative Process Fon Mong Soeng of Phorkru Mongkol Shiengcharee - ไชยลังการ, วิไลวรรณ; โพธิเวชกุล, สุภาวดี (Journal of Fine and Applied Arts Khon Kaen University, 2019)
The research aims to study the creatived process Fon Mong Soeng and the relation between chanting (Bali chanting) of Mong Soeng,drumming and dance pattern of Fon Mong Soeng of Phorkru Mongkol Shiengcharee. Which study from the documents, the interviews, the odservation and collection the information from the fields. The practicing receives from teaching of creative process Fon Mong Soeng of Phorkru Mongkol Siengcharee. There are four creative processes, 1. Thinking process has passed on from Phorkru Manop Yarana which isndevided into two concepts. Which are playing music then to continue with Mong Soeng dancing, anotrer. One is doing Fon Mong Soeng together with playing music. 2. To design of the show concept Everyone can be a perfurmer. For the song’s design that use only rhythm machines such as Mong Soeng drum, drum will play while the performers are showing through chanting (Bali chanting) “Namotatsa….” And “Ihipiso…” to control the rhythm for dancing. They dress in traditional northen costume. The third of process is the acting has 3 kinds of dancing a group of 9 men, a group of 9 women only and a group of 18 performance to mix both. And the last is design of thai dance 7 dance positions and 6 dance positions of “Lanna traditional pattern” that contains many kind of changing floor patterns. For relation between chanting (Bali chanting) with Mong Soeng drumming of Phorkru Mongkol Shiengcharee they use chanting (Bali chanting) instead of Mong Soeng drum system for meditation and to recall the good of Triple Gems. While playing Mong Soeng drum and dancing, the performers are clam in the mind for moving their bodied which is related to sing the chanting (Bali chanting) for all throughout the show. The most important thing is the performers can play the instrument and dance Mong Soeng There should preserve this dance form.